Speciality rice biodiversity of Kerala: need for incentivising conservation in the era of changing climate - Girigan Gopi and M. Manjula
Genetic diversity is integral to food security and sus- tainable agriculture. The erosion in genetic diversity across the globe raises serious threats to food security and our capacity to adapt to climate change. This article discusses the status of genetic diversities of rice varieties in Kerala, and the contributing factors for the genetic diversity. The rich genetic diversity of rice in Kerala offers scope to adapt to multiple agro- ecologies, provides resistance to biotic and abiotic stresses, carries special culinary traits and has cul- tural significance. Thus, these rice landraces are im- portant in creating an enabling environment for farming in the context of climate change. However, shift from landraces to modern varieties and large scale conversion of rice fields for alternate uses poses challenge to in situ conservation of rice landraces. The existing policy environment, research and develop- ment strategies and markets are skewed in favour of modern varieties. It is argued that the need for ‘con- servation incentive’ is a key strategy for promoting in situ conservation of rice landraces of Kerala.